Going paperless Baguio Sangguniang Panglungsod's adoption of computers and internet - Dolom, Danielle Fortich; Samson, Ma. Angelica Campos (2014., 2014)
This study is about the diffusion of computerized system and online transaction and communication of Baguio City Sangguniang Panglungsod office. The prime objective is to know how Sangguniang Panglunsod employees adopted the computerized system of managing, making, and keeping documents and data implemented by the government. The study also wants to know the preferred system of the employees and the factors that affected such decision. It also predicts the success of online transactions and communication by the time these would be fully implemented -- Author's abstract.
Thesis (Bachelor of Arts in Communication) -- University of the Philippines, 2014.
Includes bibliographical references (leaves 69-71)
Keywords: Office practice -- Philippines -- Baguio City -- Automation; Internet in public administration -- zPhilippines -- Baguio City; Electronic filing systems -- Philippines -- Baguio City; Computers -- Social aspects